Efeito sacietogênico de um novo inibidor de tripsina da paçoca do amendoim com aumento plasmático de colecistocinina (cck) - Serquiz, Alexandre Coelho (2012)
Obesity is increasing, reaching epidemic levels in many regions of the world. Studies have shown that consumption of peanuts influences on weight control and this influence may be due to the action of trypsin inhibitors sacietogênica that condition increased plasma colescistocinina (CCK). Moreover, the peanut has other health benefits, and these assignments are guaranteed to increase their production and consumption of several of its products, including the paçoca peanut. The aim of this study was to identify the presence of a trypsin inhibitor in paçoca peanut and evaluate its effect on food intake, weight gain and histomorphological changes in swiss mice (n = 8) and Wistar rats (n = 6). Experimental diets were prepared based on the AIN-93G and supplemented with tack or peanut trypsin inhibitor partially purified paçoca peanut (AHTI). After each treatment, the animals were anesthetized and euthanized, their bloods were collected by cardiac puncture for the determination of CCK and other biochemical parameters (glucose, triglycerides, total cholesterol, high density lipoprotein, low density lipoprotein, glutamic-pyruvic transaminase, glutamic oxaloacetic transaminase and albumin) and their pancreas removed for histologic and morphometric analysis. The supplementation with paçoca peanut and the AHTI showed a decrease of body weight gain and food intake in both mice and rats, due to the satiety, since the animals showed no evidence of impairment of nutritional status conditioned by consumption the AHTI. There were also observed biochemical or morphological important when compared with controls. However, AHTI led to increased secretion of CCK, a peptide sacietogênico. Thus, these results indicate that AHTI present in paçoca peanut, is able to enhance the secretion of plasma CCK and thereby reduce the weight gain associated with lower food intake of experimenta animals